The Impact of Educational Intervention Based on Health Belief Model on Nutritional Behaviors Associated with Gastric Cancer among Iranian Female Employees - Ali Khani Jeihooni; Zahra Khiyali; Mansour Kashfi Seyyed; Farzaneh Ghalegolab; Pooyan Afzali Harsini (Journal of Education and Community Health)
Aims: Gastric cancer is the most common cause of death among all cancers in Iran. Due to the role of proper nutrition to prevent gastric cancer the present study was aimed to determine the impact of educational intervention based on the Health Belief Model on nutritional behaviors associated with gastric cancer among female employees in Fasa, Fars, Iran. Materials & Methods: This quasi-experimental study was performed on 100 working women covered by two health centers in Fasa who were randomly divided into experimental and control groups. The data collection tool was a researcher-made questionnaire, including demographic characteristics, knowledge, Health Belief Model constructs, and performance measurement that were completed before, 3, and 6 months after the educational intervention by the experimental and control groups. The training program was held in 8 sessions of 50 to 55 minutes in the hall of the health center with group discussion method along with showing videos and educational images for the experimental group. Questionnaires were collected and analyzed by SPSS 22 statistical software using Chi-square, independent t-test, paired t-test, and RMA NOVA (Repeated Measurement ANOVA). Findings: The mean age of the subjects in the experimental group was 35.64±5.30 and in the control group was 35.70±5.38. Results showed that before the intervention, there was no significant difference between the experimental and control groups in terms of knowledge, perceived susceptibility, perceived severity, perceived benefits, perceived self-efficacy and performance (p>0.05). But in the 3 and 6 months after the intervention, the experimental group showed a significant increase in each of the above except the perceived barriers compared to the control group, and in the perceived barriers construct the test group significantly decreased compared to the control group (p<0.05). Conclusion: Designing and implementing educational interventions based on the Health Belief Model was effective in preventing gastric cancer with a focus on nutritional behaviors in employed women.